Trinidad and Tobago : Staff Report for the Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This 1999 Article IV Consultation highlights that after emerging from a prolonged period of decline in the 1980s, the economy of Trinidad and Tobago has performed well in recent years, with steady economic growth and low inflation. Although a sizable investment boom in the energy sector should contribute to faster growth in the coming years, a serious terms-of-trade shock in 1998 limited output growth. Inflation has declined to a relatively low level, although rising food prices led to some pickup in 1998. The unemployment rate, although declining, remains high, at about 14 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet